SUMBANGAN FALSAFAH HIDUP MASYARAKAT KEI AIN NI AIN BAGI MODERASI BERAGAMA DI INDONESIA - Kotin, Lambertus Moa; Refo, Ignasius Samson Sudirman (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
This study aims to determine the role of the Kei people's philosophy of life, "ain ni ain," in supporting the implementation of religious moderation and national commitment among the people of the Kei Islands. To achieve this goal, qualitative methods were used in this research, including datacollection through observation and interviews. All data transcripts were typed and organized according to the following stages: data reduction (identification), categorization (each category wasgiven a clear name), synthesis (finding links between categories), and compiling a working report(addressing the research questions). The results of this study indicate that the contribution of "ain ni ain" in supporting national commitment and religious moderation precedes the existence of religious and state regulations in the lives of the Kei people. Thus, "ain ni ain" serves as a guiding principle for the people of Kei to coexist and accept one another. The philosophy of life, "ain ni ain," has been interpreted and embraced by every people of Kei as a guiding principle that fosters harmony and opposes violence, resulting in a harmonious and non-violent way of life among the Kei people in line with the philosophy of "ain ni ain." However, it is important to acknowledge that the philosophy of "ain ni ain" can be misused for nepotism purposes, where individuals prioritize personal relationships over the values that should be upheld.